2011
DOI: 10.4049/jimmunol.1002876
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Reduces Airway Inflammation in Mice through Binding to Proinflammatory Chemokines and Inhibiting Inflammatory Cell Recruitment

Abstract: One major activity of chemokines is recruiting immune cells to sites of infection and inflammation. CD4+ Th1 cells play critical roles in host defense against pathogens and in the pathogenesis of many immune-mediated diseases. It has been reported that epigallocatechin-3-gallate (EGCG) exhibits anti-inflammatory properties, but the mechanisms have not been completely defined. In this study, we found that EGCG markedly decreased recruitment of murine ovalbumin (OVA)-specific Th1 cells and other inflammatory cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 44 publications
1
32
0
1
Order By: Relevance
“…A new antinflammatory mechanism of EGCG based on its binding activity to chemokines has been reported [137]. Surface plasmon resonance studies have demonstrated that EGCG directly binds to CXCL9, CXCL10 and CXCL11, thus hampering their inflammatory activities in a murine model of airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…A new antinflammatory mechanism of EGCG based on its binding activity to chemokines has been reported [137]. Surface plasmon resonance studies have demonstrated that EGCG directly binds to CXCL9, CXCL10 and CXCL11, thus hampering their inflammatory activities in a murine model of airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Transfections were performed as described previously [18, 19]. Briefly, the L1.2 murine pre-B cell line [1820] was electroporated with pcDNA3.1(+)-fCCR6.1, and stably transfected cells were obtained after two rounds of single cell cloning in the presence of 1mg/ml G418 (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Literature reports indicate that the effect of GTE on the immune system depends on the dose and can either suppress or enhance peripheral blood mononuclear cell proliferation (Qin et al, 2011), (Kim, Quon, Kim, 2014). The effectiveness of GTE supplementation may be related to individual characteristics, age, gender or physical fitness level.…”
Section: Discussionmentioning
confidence: 99%